Using Two Stackers on One Rail in a Production System - Kopecek, Pavel; Pinte, Milan; Sasiadek, Michal; Latif, Muhammad (Communications - Scientific letters of the University of Zilina, 2017)
This paper deals with the possibilities for using two stackers for interoperation transport in a workshop with a technological layout of workplaces. Basic layouts of stacker production systems are discussed. Several strategies for selecting and ordering transport demands in systems with two stackers on one rail have been simulated and evaluated. FIFO strategies are the worst in various layouts of workplaces. On the other hand, the strategy of the choice of the proximate transport demand is simple and very successful. Good technological layout can enhance transport performance.